Development Assistance "Apaya" (Abon Papaya) As Business Creative Village Kumba, District Jagoi Babang Bengkayang - Zulfahita Zulfahita; Dina Anika Marhayani; Nindy Citroresmi Prihatiningtyas; Mariyam Mariyam; Rini Setyowati; Ahmad Yani T (International Journal of Public Devotion, 2021)
One of the forms of business that may be done by a housewife is entrepreneurship, namely making APAYA (Abon Papaya). Processed food products made from papaya are chosen as an entrepreneurial business because they have good prospects. In addition to the young leaves as medicine, the fruit can be used as sweets, there are other food preparations made from papaya. Given the benefits and good nutritional content, papaya fruit verification is needed so that the product can be more acceptable to the community. The purpose of this activity is to inspire people about an idea and an entrepreneurial spirit with raw materials that are easily available and available around them so that they can increase household income. Through this service activity, assistance in making APAYA (Abon Papaya) into an economic commodity product in the form of shredded shredded can provide an alternative to new economic businesses in the community. The positive impact of this activity is to increase skills and knowledge related to the production of processed papaya fruit.